Anti‐Donor HLA Antibody Response After Pancreatic Islet Grafting: Characteristics, Risk Factors, and Impact on Graft Function. Issue 2 (25th July 2016) - Pouliquen, E.; Baltzinger, P.; Lemle, A.; Chen, C.‐C.; Parissiadis, A.; Borot, S.; Frimat, L.; Girerd, S.; Berney, T.; Lablanche, S.; Benhamou, P. Y.; Morelon, E.; et al.
Abstract : Pancreatic islet grafting restores endogenous insulin production in type 1 diabetic patients, but long‐term outcomes remain disappointing as a result of immunological destruction of allogeneic islets. In solid organ transplantation, donor‐specific anti‐HLA antibodies (DSA) are the first cause of organ failure. This retrospective multicentric study aimed at providing in‐depth characterization of DSA response after pancreatic islet grafting, identifying the risk factor for DSA generation and determining the impact of DSA on graft function. Forty‐two pancreatic islet graft recipients from the Groupe Rhin‐Rhône‐Alpes‐Genève pour la Greffe d'Ilots de Langerhans consortium were enrolled. Pre‐ and postgrafting sera were screened for the presence of DSA and their ability to activate complement. Prevalence of DSA was 25% at 3 years postgrafting. The risk of sensitization increased steeply after immunosuppressive drug withdrawal. DSA repertoire diversity correlated with the number of HLA and eplet mismatches. DSA titer was significantly lower from that observed in solid organ transplantation. No detected DSA bound the complement fraction C3d. Finally, in contrast with solid organ transplantation, DSA did not seem to negatively affect pancreatic islet graft survival. This might be due to the low DSA titers, specific features of IgG limiting their ability to activate the complement and/or the lack of allogenic endothelial targets in pancreatic islet grafts. Abstract : This multicenter study provides an in‐depth characterization of donor‐specific antibody response after pancreatic islet grafting, identifies immunosuppressive drug withdrawal as the main risk factor for donor‐specific antibody generation, and demonstrates that, in contrast with solid organ transplantation, donor‐specific antibodies have no deleterious impact on islet graft function.